The Subjective Vitality of Female Students: The Role of Attachment Styles and Alienation from Parents with the Mediation of Basic Psychological Needs - parvaneh alaie; Ladan Vaghef; fatemeh Nadimi (مطالعات روانشناسی تربیتی)
The aim of this research was to determine the role of attachment styles and alienation from parents in explaining the subjective vitality of female students through the mediation of basic psychological needs.The statistical population of this descriptive-correlational research was about 3300 people and included all female students of public highschools in Tabriz city (2022), of which 250 people were selected by available sampling method and answered to the research instrument by online which was included questionnaires of Ryan and Fredick's subjective vitality (1997), Hazen and Shaver's attachment styles (1987), alienation from parents of Gardner (2001), and the basic psychological needs of Guardia, Deci and Ryan (2000). The results of data analysis useing of SPSS16 and AMOS24 softwares showed that In addition to the good fit of the research model (RMSEA = 0.05), attachment styles had a direct effect and an indirect effect on subjective vitality due to the psychological need for communication (P < 0.05). Alienation from parents only had a direct effect on subjective vitality (P < 0.01). A positive relationship was found between secure style and basic psychological needs with the Subjective vitality of female students; this relationship between avoidant and ambivalent styles and alienation from parents was negative (P < 0.01). Considering the research findings, it is important to make suitable policies and hold educational workshops for the target groups in order to strengthen secure attachment styles, reduce alienation from parents and meet psychological needs in promoting the subjective vitality of adolescent girls.